Clinical and histological spectrum of hepatitis C disease associated with persistently normal alanine aminotransferase levels - Asim, Maleha; Jafar, Sadaf; Mughal, Aashi; zia, quratulain; ali, hamid; jamil, aneela; Zaffar, Ghazal (International Journal of Research in Medical Sciences, 2017)
Background: Around 20% of patients with chronic hepatitis C infection (HCV) have persistently normal alanine aminotransferase (PNALT) levels. These patients are considered to have mild degree of histological hepatic damage. This study was conducted to compare the histological degree of necro-inflammation and stage of fibrosis among HCV patients with PNALT and patients with persistently or intermittently elevated serum ALT (PIEALT) levels.. Methods: This study includes 154 untreated patients with serological and histological diagnosis of chronic HCV infection. A total of 70 patients with PNALT (group A) and 84 patients with PIEALT (group B) were identified and treated with 6 months interferon therapy. Histological grade of necro-inflammatory activity and the stage of fibrosis was evaluated by Ishak scoring system. HCV-RNA quantification was done by real-time polymerase chain reaction (PCR). Further univariate and multivariate analysis was done to evaluate correlation between patients characteristics and significant hepatic fibrosis.. Results: Out of one hundred and fifty four patients, mean ALT was 30.59 ± 5.59 U/L in group A as compare to 68.65 ± 23.17 U/L in group B (p = 0.001). Patients with PNALT were younger (p = 0.005) with milder grade of necrosis (p = 0.037), lower serum HCV viral load (p = 0.044) and significant achievement of sustained virological response (p = 0.012) as compare to patients with abnormal ALT. Different variable were also analysed by univariate and mutivaraite analysis among patients with significant and insignificant fibrosis. High serum HCV-RNA level was found to be the independent variable predictive of advanced fibrosis among HCV infected patients (OR = 0.89; 95% CI = 1.65-1.94; p < 0.001) with r2 = 80%. Conclusions: Our study suggests that normal serum ALT does not mean healthy liver. So, histological evaluation is still an essential tool to assess liver damage precisely.